School of architecture, Bhutan - Balakrishnan.R (SPA, Bhopal, 2014)
Architecture is one of the many things with give Bhutan’s past a continuity with the present because the old and medieval buildings in Bhutan do not merely exist but they are actively used and inhabited by people even today. To maintain that Tradition there must be a school of Architecture in Bhutan. The Education Hub in Bhutan is been Proposed 30 km away from Thimphu and Paro International Airport. This project includes different Educational Institutions from primary school to University. In this project one such Institution is School of Architecture which I have taken as my Thesis topic and I am designing the Academic section of it. The Royal Government of Bhutan has a long-term vision of developing Bhutan into a world-class regional hub for education, health, and financial services, and information and communications technology. So this project is one which fulfills the dream of every one.
Keywords: School of architecture